Ocular Inflammation and Endoplasmic Reticulum Stress Are Attenuated by Supplementation with Grape Polyphenols in Human Retinal Pigmented Epithelium Cells and in C57BL/6 Mice. Issue 6 (3rd April 2014) - Ha, Jung-Heun; Shil, Pollob Kumar; Zhu, Ping; Gu, Liwei; Li, Qiuhong; Chung, Soonkyu
Abstract: Inflammation and endoplasmic reticulum (ER) stress are common denominators for vision-threatening diseases such as diabetic retinopathy and age-related macular degeneration. Based on our previous study, supplementation with muscadine grape polyphenols (MGPs) alleviated systemic insulin resistance and proinflammatory responses. In this study, we hypothesized that MGPs would also be effective in attenuating ocular inflammation and ER stress. We tested this hypothesis using the human retinal pigmented epithelium (ARPE-19) cells and C57BL/6 mice. In ARPE-19 cells, tumor necrosis factor-α–induced proinflammatory gene expression of interleukin ( IL ) -1β, IL-6, and monocyte chemotactic protein-1 was decreased by 35.0%, 68.8%, and 62.5%, respectively, with MGP pretreatment, which was primarily due to the diminished mitogen-activated protein kinase activation and subsequent reduction of nuclear factor κ-B activation. Consistently, acute ocular inflammation and leukocyte infiltration were almost completely dampened (>95%) by MGP supplementation (100–200 mg/kg body weight) in C57BL/6 mice. Moreover, MGPs reduced inflammation-mediated loss of tight junctions and retinal permeability. To further investigate the protective roles of MGPs against ER stress, ARPE-19 cells were stimulated with thapsigargin. Pretreatment with MGPs significantly decreased the following: 1 ) ER stress-mediated vascular endothelial growth factor secretion (3.47 ± 0.06 vs. 1.58 ± 0.02 μ g/L, P < 0.0001), 2 ) unfolded protein response, and 3 ) early apoptotic cell death (64.4 ± 6.85 vs. 33.7 ± 4.32%, P = 0.0003). Collectively, we have demonstrated that MGP is effective in attenuating ocular inflammation and ER stress. Our work also suggests that MGP may provide a novel dietary strategy to prevent vision-threatening retinal diseases.